Green Mussel Shells as Liquid Organic Fertilizer (CARAJA): Efforts to Utilize Local Potential in Banyu Urip Village Gresik - Fardlillah, Qonita; Al Abror, Mohammad Zakky; Al Farobi, Muhammad Abduh (Universitas Serang Raya, 2025)
Banyu Urip Village is one of the villages located in the coastal area of Ujung Pangkah District, Gresik Regency. The local potential of Banyu Urip Village is green mussels, which are a result of the sea catch of fishermen in the local village. This potential is also a problem due to the accumulation of wasted green mussel shell waste that has not been managed optimally. With this problem, the community service team carried out community service activities aimed at providing alternative solutions as well as community empowerment. The method used in the community service activity of making green shell liquid organic fertilizer